A nonlinear concrete damaged plasticity model for simulation reinforced concrete structures using ABAQUS (Fracture and Structural Integrity, 2021)
The reinforced concrete structure is typical and widely used in many fields. The behavior of concrete is nonlinear and complex. Especially, when cracks/crushings occurred in softening phase. Thus, It is important to find a damaged model of concrete with high reliability in the numerical simulation. The nonlinear behavior of concrete is the most feature used in the simulation. This characteristic is expressed through the parameters defining the yield surface, the flow potential, and the nonlinear relationship of stress-strain in the cases of tension and compression. This paper introduces a damaged concrete model that applies to the simulation of reinforced concrete structures. The reinforced concrete beam and flat slab are selected as examples to evaluate the reliability of the model presented. Through the results achieved, the model used in this paper shows high reliability and can be used to simulate more complex reinforced concrete structures.
Keywords: Nonlinear behavior; Concrete material; Concrete damaged plasticity